PERFORMANCE ANALYSIS OF INTEGRATED MUNICIPAL WASTE MANAGEMENT AS WASTE REDUCTION EFFORT (CASE STUDY: TPS 3R RAWASARI, CENTRAL JAKARTA) - WIDYADWIANA (NIM : 25713301), AMANDA
The high number of inhabitants, especially in urban areas has affected on the high amount of waste generated, therefore it is necessary to have an efficient waste management effort to extend the life-span of the final disposal site (Tempat Pemrosesan Akhir), lowering the waste processing cost and to prevent environmental degradation. A waste management policy that could be applied is the utilization of the temporary Waste Collection Point (Tempat Pengumpulan Sementara) which also implements 3R (Reduce – Reuse – Recycle) process, hereinafter will be referred as TPS 3R. The development of TPS 3R currently are mostly conducted by the Central Government, however for its operation is handed over to the Local Government or the local community. Whereas the operational of TPS 3R Rawasari is submitted to a non-governmental organization as the manager. With a total waste generation in Cempaka Putih Timur village of 14.573,93 kg / day, however, currently TPS Rawasari can only recieve waste at 619,63 kg / day of a design capacity of 2-4 tons / day. On the other hand, there is an integrated household scale waste treatment in Banjarsari village which until now is still running well. Therefore, the performance analysis of TPS 3R Rawasari is considered necessary to know the efficiency of waste management and adopt the lessons learned from the Banjarsari village. Performance evaluation comprise the technical aspects of using the approach of mass balance and the composting process analysis, descriptive analysis and correlation to the social aspects so that the form of community participation can be determined, as well as the calculation of unit cost of waste management in TPS 3R Rawasari. The whole data obtained subsequently will be used as an input for a SWOT analysis to determine the problems and define optimization strategies. From the evaluation results showed that TPS 3R Rawasari is no longer optimal in conducting waste management. Through the financial analysis of the two conditions, indicate that the value of the unit cost for optimizing TPS 3R under the responsibility of the management (Condition 1) is Rp 279.364 / tons of waste, whereas if handed over to the local government (Condition 2) the value of the unit cost is Rp 88.467 / tons of waste. Hence the operation of TPS 3R Rawasari by the Government is preferred because the value is below the unit cost of tipping fee to transport the waste. Things that must be done for the submission of the 3R TPS Rawasari to local government based on SWOT analysis, among others, increasing the involvement of the community adopted from the Banjarsari village. These stages namely determining the initiator of the management of waste from the local community, shifting the local budget allocation for the tipping fee to the operational funds for TPS 3R Rawasari and procurement for continuous socialization held by the Government.